Pathways to Adult Education for Emerging Adults Surviving Poverty - Crayal V. Sisuse (Adult Education Research Conference, 2023)
This research seeks to investigate African American emerging adults living in under-resourced communities while pursuing education and career pathways. In this study, the researcher will employ the emerging adult theory.
Keywords: emerging adults; poverty; pathways; African American; education